The prevalence of obstructive sleep apnoea and its association with aortic dilatation in Marfan's syndrome. Issue 2 (13th October 2008) - Kohler, M; Blair, E; Risby, P; Nickol, A H; Wordsworth, P; Forfar, C; Stradling, J R
Abstract : Background: Craniofacial abnormalities and increased pharyngeal collapsibility due to abnormal connective tissue suggest the possibility of an increased prevalence of obstructive sleep apnoea (OSA) in patients with Marfan's syndrome but the actual prevalence is uncertain. Aortic dilatation and dissection are life threatening manifestations of Marfan's syndrome and case reports have suggested a possible association with OSA but data from cohort studies are not available. Methods: A sleep study was performed in 61 patients with Ghent criteria positive Marfan's syndrome (mean age 38.3 (SD 12.9) years; 37 females) and in 26 control subjects matched for age, gender, height and weight. OSA was defined using two conventional levels of apnoea–hypopnoea index (AHI), >5 and >15/h. In patients with Marfan's syndrome, aortic root diameter was measured by echocardiography. Results: More patients with Marfan's syndrome than controls had OSA (AHI >5, 32.8% compared with 11.5%, mean difference +21.3%, 95% CI 4.2% to 38.3%, p = 0.04; AHI >15, 18.0% compared with 0%, mean difference +18.0%, 95% CI 8.4% to 27.7%, p = 0.02). AHI was correlated with aortic root diameter (r = 0.50, 95% CI 0.26 to 0.69, p = 0.0003), and mean aortic root diameter was significantly greater in patients with OSA (4.5 (SD 0.6) cm) compared with those without OSA (3.7 (0.6) cm) (mean difference 0.8 cm, 95% CI 0.4 to 1.2 cm, p<0.0001). Conclusions: In patients with Marfan's syndrome, the prevalence of OSA is considerably higher than in matched control subjects. OSA may be a risk factor for aortic root dilatation in Marfan's syndrome.